GAMBARAN RESPON PERILAKU NYERI BAYI PADA PEMBERIAN SUNTIKAN IMUNISASI DASAR DI PUSKESMAS BAHU KECAMATAN MALALAYANG KOTA MANADO - Sisfiani Sarimin; Lucia Moningka; Astria Jansen (Jurnal Ilmiah Perawat Manado (Juiperdo), 2015)
Immunization as a preventive way to prevent the disease, through the provision of immunity to be given continuously, comprehensively and implemented according to standard so as to provide protection of the health and breaking the chain of transmission. In general, the provision of basic immunization injections action on the infant will cause pain effect. This study aimed to get an overview of infant pain response on providing basic immunization at PHC of Bahu Manado. The benefits of research to the health center is expected to provide information and input for the clinic to improve immunization coverage in their work areas. The population in this study, all mothers carrying infant for immunization by 65 respondents. This type of research is descriptive observational survey. How to accidental sampling sampling 30 respondents who met the included criterion. The data obtained were tabulated then processed and presented in frequency distribution of table. The variables in this study using a single variable that infants pain response on providing basic immunization injections. The research carried out in August 2014. In this study, response to pain highest respondents who received BCG immunization with a score MBPS of 7.08 number of 12 respondents (40%). And the pain response by age, the data obtained by respondents who had a mean score MBPS of 7.5 in infants aged 0-3 month. For a nurses is expected to provide information and input for the clinic to improve atramautic care method in infant during immunization.